Writing for Reconciliation: A Musing - Bell Hooks (Journal of the Assembly for Expanded Perspectives on Learning, 2007)
This musing grew out of the AEPL Summer Conference in Berea, Kentucky, June 2006, at which bell hooks was the keynote speaker.